2021
DOI: 10.1111/hiv.13154
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir in the long term in children and adolescents: frequent virological failure but rare acquired genotypic resistance

Abstract: Objectives Although widely recommended, data about dolutegravir efficacy in HIV‐1‐infected children/adolescents are scarce, limited to short‐term follow‐up and mainly extrapolated from studies in adults with good adherence to treatment. This study aimed to provide long‐term data about the risk of virological failure (VF) and acquired genotypic resistance in children and adolescents receiving dolutegravir. Methods This retrospective monocentric study included 134 paediatric patients who received a dolutegravir‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Furthermore, the fact that subjects with VF had longer duration of follow‐up than those with sustained viral suppression (43 vs. 36 months, P = 0.047) suggests that, in paediatrics, the longer the patient's follow‐up, the higher the risk of observing virological rebound. We observed a higher risk of VF in subjects initiating BIC/FTC/TAF with pVL >50 copies/mL on ART than in those with suppressed baseline viraemia, as previously evidenced in children/adolescents initiating dolutegravir‐based ART [14]. This result suggests that, at least in some children/adolescents, major adherence issues persist after switching ART and these cannot be definitely counterbalanced by the good efficacy and tolerance profile of BIC/FTC/TAF.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the fact that subjects with VF had longer duration of follow‐up than those with sustained viral suppression (43 vs. 36 months, P = 0.047) suggests that, in paediatrics, the longer the patient's follow‐up, the higher the risk of observing virological rebound. We observed a higher risk of VF in subjects initiating BIC/FTC/TAF with pVL >50 copies/mL on ART than in those with suppressed baseline viraemia, as previously evidenced in children/adolescents initiating dolutegravir‐based ART [14]. This result suggests that, at least in some children/adolescents, major adherence issues persist after switching ART and these cannot be definitely counterbalanced by the good efficacy and tolerance profile of BIC/FTC/TAF.…”
Section: Discussionsupporting
confidence: 81%
“…In our cohort, much higher rates of VF were observed (38% of subjects, 26% of those with viral suppression at baseline). Similar rates of VF were observed in children and adolescents receiving a dolutegravir-based combination in previous real-life cohorts [13,14], illustrating that maintaining high adherence to treatment in the long term remains challenging in paediatrics. Furthermore, the fact that subjects with VF had longer duration of follow-up than those with sustained viral suppression (43 vs. 36 months, P = 0.047) suggests that, in paediatrics, the longer the patient's follow-up, the higher the risk of observing virological rebound.…”
Section: Discussionsupporting
confidence: 69%
“…Following the review of their titles and abstracts, 232 publications were submitted for full-text review. Following full-text review, 36 publications were found to have reports of INSTI-naïve PLWH who developed one or more INSTI-associated DRMs while receiving DTG [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and 21 publications contained in vitro susceptibility results performed using the PhenoSense assay [ 32 , 33 , 35 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , ...…”
Section: Resultsmentioning
confidence: 99%
“…13,27 Although drug resistance testing and robust adherence measures were beyond our evaluation scope, poor adherence, with the possibility of some INSTI resistance, was the likely driver of treatment failure. 28,29 There has been concern that NRTI resistance associated with prior failing ART regimens may result in functional monotherapy with DTG in ART-experienced, virally unsuppressed individuals who switch to DTG and maintain the NRTI backbone of the failing regimen, potentially resulting in DTG failure and development of INSTI resistance. 30,31 However, meaningful differences in VLS between children who maintained or switched NRTI backbones at the time of the DTG switch were not observed in our study.…”
Section: Discussionmentioning
confidence: 99%